2010
DOI: 10.1016/j.pnpbp.2010.02.024
|View full text |Cite
|
Sign up to set email alerts
|

No effect of obstetric complications on basal ganglia volumes in schizophrenia

Abstract: The present results do not support the hypothesis that OCs are related to alterations in basal ganglia volume in chronic schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 212 publications
(240 reference statements)
0
6
0
1
Order By: Relevance
“…42 Although obstetric complications were correlated with changes in hippocampal volume in that study, 42 no correlations were found for cortical thickness 119 or volume of basal ganglia. 120 Thus, issues of selective vulnerability to early insults need to be understood in more detail before genetic variation can be related to the risk of schizophrenia. A recent study compiled 12 candidate endophenotypes and tested associations with n = 94 candidate genes.…”
Section: Endophenotypes For Matched Genesmentioning
confidence: 99%
“…42 Although obstetric complications were correlated with changes in hippocampal volume in that study, 42 no correlations were found for cortical thickness 119 or volume of basal ganglia. 120 Thus, issues of selective vulnerability to early insults need to be understood in more detail before genetic variation can be related to the risk of schizophrenia. A recent study compiled 12 candidate endophenotypes and tested associations with n = 94 candidate genes.…”
Section: Endophenotypes For Matched Genesmentioning
confidence: 99%
“…Bilateral hippocampal atrophy has been detected in adolescents with a history of perinatal asphyxia diagnosed as hypoxic-ischemic encephalopathy, along with worse verbal long-term memory (Maneru et al, 2003). In schizophrenia, patients with obstetric complications have shown reduced hippocampal volumes (McNeil et al, 2000; Van Erp et al, 2002; Schulze et al, 2003; Ebner et al, 2008), while no effects have been observed in volumes of basal ganglia (Haukvik et al, 2010). However, effects of antipsychotic medication have to be taken into consideration when investigating brain regions (Lieberman et al, 2005).…”
Section: Birth and Obstetric Complicationsmentioning
confidence: 99%
“…In the present study, the number of OCs with severity scores of o3 was calculated for each individual subject to form one continuous variable. Scores <3 are considered not to be harmful to the foetus (McNeil & Sjostrom, 1995 ;Haukvik et al 2010). Obstetric characteristics are presented in Table 1.…”
Section: Assessment Of Ocsmentioning
confidence: 99%